Health and disability care providers' experiences and perspectives on end-of-life care needs of individuals with long-standing physical disability: A qualitative interview study. (January 2023) - Belperio, Irene; Devery, Kim; Morgan, Deidre D; Rawlings, Deb; Raghavendra, Parimala; Walker, Ruth
Background: Little is known about the specific needs and experiences of individuals with long-standing physical disability at end of life. Aim: To explore health and disability care providers perspectives and experiences in relation to end-of-life care needs of individuals with long-standing physical disability. Design: Qualitative study using reflexive thematic analysis. Setting/participants: Semi-structured interviews were conducted with nine health and disability care providers from two Australian states. Results: Five themes were constructed from the data: (1) The significance of place. All participants described how the end-of-life care experience was significantly impacted by the place in which dying occurred. (2) Knowing the person and their needs. Knowledge and familiarity with the individual with long-standing disability were seen as invaluable in terms of providing continued high-quality care. (3) Navigating a new care landscape. For disability support workers, struggling to adapt from providing disability support to end-of-life care was difficult. (4) Complexities of family involvement. Past experiences of families within the healthcare system had resultant impacts on care received by the individual with long-standing disability. (5) Being prepared. Participants felt more was needed in terms of end-of-life planning and discussions around end of life for this cohort. Conclusions: This research highlights a significant lack of continuity of care and problems at the intersection of the disability and health systems when providing end-of-life care for this cohort. Suggested areas for improvement include team approaches to enable continuity of care and dying in place, and a need for knowledge and skills in this area for all stakeholders.